From coupon to calories: Assessing input coupon impact on household food calories production. (June 2021) - Hodjo, Manzamasso; Dalton, Timothy; Nakelse, Tebila; Acharya, Ram N; Blayney, Don
Highlights: We assessed the impact of farm input coupons on household food calories production. Benefits from fertilizer, seed and flexible voucher increase caloric production. Flexible coupon has the greatest impact on own-produced food calories. Larger farm holders in 2019 had the highest coupon impact on caloric production. Expanding subsidy programs could improve food availability. Abstract: The primary objective of most farm households in Malawi is to secure sufficient food for their own needs. In this paper we assess the impact of farm input subsidy vouchers on household food caloric production. We used pooled cross-sectional household data from the 2010, 2013, 2016 and 2019 Malawian Living Standards Measurement Study and Integrated Survey on Agriculture (LSMS-ISA) to fit a two-stage panel fixed effect model under an endogenous treatment assignment setting. Our findings suggest that benefits from an existing input coupon positively affect household food calories production. Also, we found the flexible coupon traded for either compound fertilizer, urea, or improved maize seed to have the greatest impact. Furthermore, larger farm holders and coupons receivers in 2019 had the highest coupon impact on caloric production. Expanding subsidy programs could result in improved food availability for farming households.